Arabidopsis Chloroplast Mini-Ribonuclease III Participates in rRNA Maturation and Intron Recycling. Issue 3 (27th February 2015) - Hotto, Amber M.; Castandet, Benoît; Gilet, Laetitia; Higdon, Andrea; Condon, Ciarán; Stern, David B.
Abstract : Using RNA-Seq and end-mapping, we showed that two Arabidopsis Mini-III proteins, which are putative double-stranded plastid endonucleases, process rRNA, introns, and a plastid noncoding RNA. Abstract: RNase III proteins recognize double-stranded RNA structures and catalyze endoribonucleolytic cleavages that often regulate gene expression. Here, we characterize the functions of RNC3 and RNC4, two Arabidopsis thaliana chloroplast Mini-RNase III-like enzymes sharing 75% amino acid sequence identity. Whereas rnc3 and rnc4 null mutants have no visible phenotype, rnc3/rnc4 ( rnc3/4 ) double mutants are slightly smaller and chlorotic compared with the wild type. In Bacillus subtilis, the RNase Mini-III is integral to 23S rRNA maturation. In Arabidopsis, we observed imprecise maturation of 23S rRNA in the rnc3/4 double mutant, suggesting that exoribonucleases generated staggered ends in the absence of specific Mini-III-catalyzed cleavages. A similar phenotype was found at the 3′ end of the 16S rRNA, and the primary 4.5S rRNA transcript contained 3′ extensions, suggesting that Mini-III catalyzes several processing events of the polycistronic rRNA precursor. The rnc3/4 mutant showed overaccumulation of a noncoding RNA complementary to the 4.5S-5S rRNA intergenic region, and its presence correlated with that of the extended 4.5S rRNA precursor. Finally, we found rnc3/4 -specific intron degradation intermediates that are probable substrates for Mini-III and show that B. subtilis Mini-III is also involved in intron regulation. Overall, this study extends our knowledge of the key role of Mini-III in intron and noncoding RNA regulation and provides important insight into plastid rRNA maturation.